Understanding How the Projection of Availability State Impacts the Reception of Incoming Communication - Teevan, Jaime; Hehmeyer, Alexander (Proceedings of the 2013 ACM Conference on Computer Supported Cooperative Work (CSCW '13), 2013)
Many communication systems infer and project information about a user's availability, making it possible for others to decide whether and how to contact that user. Presumably when the system infers people are busy, they are less open to interruption. But analysis of 103,962 phone calls made using a popular enterprise communications tool reveals that people are actually significantly more likely to answer the phone when the system projects that they are busy than at other times. A follow-up survey of 569 users of the system suggests that this seemingly counter-intuitive fact may arise because people care a lot about the recipient’s availability when initiating phone communications and are unlikely to attempt to call someone who appears to be busy unless the communication is important. Recipients thus perceive incoming calls as more important when they are busy than at other times, making them more likely to answer.